Process and reliability studies of solder bumping using eutectic sn/pb solder - Lo, Marvin Chen Yang. (2008)
This project studies the differences in solder bumping using different bumping technologies. The two technologies of interest are printing technology and plating technology for solder deposition process. It was found that printing technology required two mask sets as compared to 1 mask for plating technology. In printing technology, bump voids are an inherent defect and must be controlled to within less than 30% of the bump volume. The additional mask cost will add to the production cost. In large volume manufacturing, the price for bumping between printing and plating is now close to each other.